The Idea of Nationalism in Indonesian History Textbooks (1975-2013) - Yuniyanto, Tri; Abidin, Nur Fatah (Diakronika, 2024)
Nationalism plays an essential role in nation-building and national integration in Indonesia. This research aims to scrutinize the change and the continuity of the idea of nationalism in Indonesia through discourse historical analysis of the Indonesian history textbooks from the New Order to the Post-reformation era. The question addressed in this research: Has Indonesian society ‘reimagined’ or ‘recalibrated’ the conception of nationalism along with the political transitions and transnational problems? Qualitative methods with the Discourse Historical Analysis approach were used to examine the history textbooks. Textbook analysis showed that the political transition from the Guided Democracy era to the New Order era in 1966 or the fall of the New Order era in 1998 did not significantly change the idea of nationalism. The primeval idea of nationalism remains the basic foundation of nationalistic discourse in history textbooks. Every political regime tends to impart or attach its political interest to nationalism. As a result, the primeval ideas of nationalism, developmental nationalism, and modern nationalism are intermingled. It tends to create a continuation and dynamic rather than changes in nationalism. As a result, the idea of nationalism in Indonesia, as represented in history textbooks, tends to be a political project rather than a collective one.